Commonalities and differences among the Abrahamic faiths - Abdullah @ Chuah Hock Leng, Osman; Ishak, Mohd. Shuhaimi (International Islamic University Malaysia, 2011)
Abrahamic faiths namely Judaism, Christianity and Islam share the theology of monotheism. The three religions trace their origins to Prophet Abraham. Judaism is the religion of the descendents of Jacob, son of Isaac and grandson of Abraham. Christianity began as a sect of Judaism in the 1st century, and later on developed its own creed such as trinity. Islam began in the 7th century; it also traces its link to Ishmael, the son of Prophet Abraham. The three religions share mostly the same heritage, history, greatness and theology of monotheism. This essay attempts to highlight the common features of these three religions, while at the same time presents the differences in terms of the unique roles, perspectives and meanings of each of them.